Meningkatkan Taraf Kesehatan Masyarakat melalui Edukasi Pola Hidup Sehat di Kampung Ketandan - Fadillah, Maulana Arif; Oktavia, Adinda; Sanjaya, Jatiyasa Ega; Putri, Angelikha Merha; Fadiyah, Nida; Sharla, Disya; Fatihi, Fatihi; Barlianz, Maulana Andree; Afifah, Eliana Fairuz; Permana, Gilang Prayoga Putra; Wahyuni, Alfaina (Universitas Muhammadiyah Yogyakarta, 2025)
The low awareness of the importance of a clean and healthy lifestyle in Ketandan Village can be seen from the large amount of organic waste around the RW 15-17 road due to the narrow space for movement due to the dense distance between houses, making people have to cook around the public road and from the results of the examination there were 45 elderly people and 20 of them had blood sugar levels above normal limits, making it the main reason for our community service program in Ketandan Village regarding providing education on a clean and healthy lifestyle. This Community Service Program aims to raise awareness and understanding among the residents of Kampung Ketandan about the importance of a healthy lifestyle while providing practical solutions for environmental conservation through the implementation of biopore technology. Health education serves as an initial step in fostering good habits that can prevent various diseases and improve the overall quality of life. The activities carried out include health counseling, medical check-ups, fitness exercises, and menopause awareness sessions. Additionally, this program contributes to religious knowledge enhancement through Quranic studies and Islamic teachings, as well as participation in the Chinese Cultural Week by offering free health screenings. In the environmental aspect, this program promotes the use of biopore technology as a solution for water management and organic waste processing. Through the provided education, the community is expected to become more aware of personal hygiene, proper sanitation, and the importance of consuming nutritious food as part of a sustainable healthy lifestyle. The activities were conducted in a participatory manner, actively involving the community in discussions, hands-on practice, and mentoring sessions for program implementation. The results indicate an increased awareness among residents regarding health and environmental conservation. The high level of enthusiasm was evident from the active participation in each activity, including attendance, engagement, and implementation of the delivered materials. Although there were challenges, such as time constraints and adjustments to residents' daily activities, the program successfully achieved its goals by enhancing the community’s understanding of a healthy lifestyle and encouraging concrete actions in maintaining hygiene and environmental sustainability. It is hoped that the provided education will continue and become an integral part of the community's daily life, promoting a healthier and more environmentally friendly lifestyle.